المشاكل التي يواجهها الناطقون بالإنجليزية عند قراءة القرآن الكريم: عرضها ومعالجتها: The difficulties faced by native speakers of English in the sounds of the Holy Quran: Presentation and solutions - فيضان الرحمن (الدراسات الإسلامية, 2023)
This article makes a comparison between the similarities and differences of the consonants and vowels of Arabic and English. This would help the teachers of the Holy Qur’ān in English- speaking countries. It explores the translation of very difficult terms used in the science of tajwīd such as qalqalah. If this term is literally translated to the native speakers by saying that it means giving movement to a sound in the place of articulation, they will not understand it. Moreover, it explains the terms like the place of articulation (makhraj), the manner of articulation (ṣifah), and homorganic letters (mushtarak al-makhraj) found in the books of phonetics. The article holds that dhāl is like “th” in “within.” (i.e between two vowels). The same is the case with some other sounds discussed in the article and the abstract. However, in other contexts, they become devoiced and resemble sīn, thā, and ch. Dark L of English is judged as equal to lām mufkhamah and it was made clear that if the teachers of Qur’ānic recitation translate it to dignified L or honoured L the native students will not understand them. It was suggested to the teachers to obverse the kāf sound in the reading of the students when it is in the stressed syllables such as kālū and kallā so that aspiration after kāf is checked, because such kind of aspiration does not exist in Arabic. Similarly, when nūn sākinah occurs before kāf in words like in kuntum, English speakers are liable to add ng sound (like that in “bank” of English) before kāf.